2014
DOI: 10.2147/ndt.s30160
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin enacarbil for the treatment of moderate to severe primary restless legs syndrome (Willis-Ekbom disease): 600 or 1,200 mg dose?

Abstract: Gabapentin enacarbil is a prodrug of the anticonvulsant gabapentin. The efficacy and safety of gabapentin enacarbil for the treatment of moderate to severe primary restless legs syndrome (RLS) has been evaluated in several clinical trials in the United States and Japan. Although most clinical trials assessed gabapentin enacarbil at doses greater than 600 mg/day and demonstrated the overall safety and efficacy (defined as improvements in the coprimary endpoints of the international RLS rating scale [IRLS] total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Factors that indicate a dopamine agonist as the preferred therapy ■ Increased number of periodic limb movements in sleep at night 5,16,42,48,58,59,81 ■ Periodic limb movements and motor symptoms during the day 15,51,61,83 ■ Comorbid depression 40,47,107,108, Factors that indicate α-2-δ ligands as the preferred therapy ■ Sleep disturbance with insomnia in addition to RLS 5,24,63,71,73,75,79 ■ Comorbid pain syndrome 74 ■ Polyneuropathy 74 ■ History of or recurrent impulse control disorder 68,69,104 ■ Comorbid generalized anxiety disorder 70,77 Factors that indicate oxycodone-naloxone or other opioids as the preferred therapy ■ Previous failure of other treatments 10 is an established treatment for attacks of RLS or RLS that is triggered in specific situations, such as pro longed sitting, but no controlled data on this approach has been published. Pramipexole has also been used in this context, as it is shortacting and has a rapid onset of action.…”
Section: Box 2 | Factors That Influence the Recommended Therapy For Rlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that indicate a dopamine agonist as the preferred therapy ■ Increased number of periodic limb movements in sleep at night 5,16,42,48,58,59,81 ■ Periodic limb movements and motor symptoms during the day 15,51,61,83 ■ Comorbid depression 40,47,107,108, Factors that indicate α-2-δ ligands as the preferred therapy ■ Sleep disturbance with insomnia in addition to RLS 5,24,63,71,73,75,79 ■ Comorbid pain syndrome 74 ■ Polyneuropathy 74 ■ History of or recurrent impulse control disorder 68,69,104 ■ Comorbid generalized anxiety disorder 70,77 Factors that indicate oxycodone-naloxone or other opioids as the preferred therapy ■ Previous failure of other treatments 10 is an established treatment for attacks of RLS or RLS that is triggered in specific situations, such as pro longed sitting, but no controlled data on this approach has been published. Pramipexole has also been used in this context, as it is shortacting and has a rapid onset of action.…”
Section: Box 2 | Factors That Influence the Recommended Therapy For Rlsmentioning
confidence: 99%
“…30 Indeed, most clinical trials of gaba pentin enacarbil, including those in pain and epilepsy, have demonstrated the efficacy and safety of doses above 600 mg daily, but the FDA considered higher doses to be associated with more adverse effects, such as somnolence and dizziness, with no additional benefit. 73 In practice, treatment is usually started with a dose of 300 mg each evening, which is increased to 600 mg or 1,200 mg if RLS symptoms do not improve sufficiently to achieve a satisfactory quality of sleep.…”
Section: Gabapentin and Gabapentin Enacarbilmentioning
confidence: 99%
“…Dose selection of gabapentin enacarbil for treating RLS has been a controversial topic . In the included studies, high doses of gabapentin enacarbil (1800 mg and 2400 mg) showed no superiority to lower doses in reducing the IRLS score .…”
Section: Discussionmentioning
confidence: 99%
“…Doses higher than 600 mg were thought to provide no additional benefits and increase the chance of adverse reactions. However, the results of post hoc meta-analyses have indicated that the 1,200 mg once-daily dosage was effective not only in relieving subjective RLS symptoms but also severe sleep disturbance associated with RLS [135].…”
Section: Rlsmentioning
confidence: 99%